Localized growth of carbon nanotubes via lithographic fabrication of metallic deposits - TU, Fan; Drost, Martin; Szenti, Imre; Kiss, Janos; Konya, Zoltan; Marbach, Hubertus (Beilstein Journal of Nanotechnology, 2017)
We report on the fabrication of carbon nanotubes (CNTs) at predefined positions and controlled morphology, for example, as individual nanotubes or as CNT forests. Electron beam induced deposition (EBID) with subsequent autocatalytic growth (AG) was applied to lithographically produce catalytically active seeds for the localized growth of CNTs via chemical vapor deposition (CVD). With the precursor Fe(CO)5 we were able to fabricate clean iron deposits via EBID and AG. After the proof-of-principle that these Fe deposits indeed act as seeds for the growth of CNTs, the influence of significant EBID/AG parameters on the deposit shape and finally the yield and morphology of the grown CNTs was investigated in detail. Based on these results, the parameters could be optimized such that EBID point matrixes (6 × 6) were fabricated on a silica surface whereby at each predefined site only one CNT was produced. Furthermore, the localized fabrication of CNT forests was targeted and successfully achieved on an Al2O3 layer on a silicon sample. A peculiar lift-up of the Fe seed structures as was observed and the mechanism was discussed. Finally, a proof-of-principle was presented showing that EBID deposits from the precursor Co(CO)3NO are also very effective catalysts for the CNT growth. Even though the metal content (Co) of the latter is reduced in comparison to the Fe deposits, effective CNT growth was observed for the Co-containing deposits at lower CVD temperatures than for the corresponding Fe deposits.
EAM Import::2019-03-12